(untitled) (Fiep Bulletin - online, 2012)
Nowadays the Quality of Life has been frequently addressed, it is known that it includes many factors which are interrelated, involving physical, psychological and social well being, it is necessary a balance among these variables so the quality of life can be achieved. This way, in order for the individual to be and feel good, it is essential his knowledge on how to have quality of life, practicing such knowledge, which includes information on how to lead a healthy life through nutrition, regular physical activity, preventive behavior, relationship and stress management. Thus, this research aims at assessing the behavior of the employees of PROEX (Dean of Extension and Cultural Affairs), of the State University of Ponta Grossa who take part in Labor Gymnastics classes in order to evaluate how good their quality of life is. Therefore it has been used as methodology the quantitative and qualitative analysis and as methodological tool the protocol Pentacle of Welfare, which is composed of five matters, they are nutrition, physical activity, preventive behavior, social relationship and stress control. The survey has showed that the interference of Labor Gymnastics in the quality of life of the employees was very important, mainly regarding the aspect of social relationship.